EFFECTIVENESS OF PROBLEM BASED INSTRUCTION (PBI) VS EXPOSITORY MODEL: A COMPARATIVE STUDY OF JUNIOR HIGH SCHOOL STUDENTS' SPLDV PROBLEM SOLVING ABILITY - Hutagalung, Margaretta Serevina; Supardi U. S (Antis Publisher, 2025)
Objective: This study analyzes the comparison of the effectiveness of the Problem Based Instruction (PBI) model and the Expository model in improving mathematical problem solving skills. The fundamental problem in learning mathematics often lies in the low skills of students in solving problems. The PBI approach is based on active learning through real problems, while the Expository model emphasizes the direct delivery of information by the teacher. Method: This study used a comparison experimental design between two treatment groups. The instrument used was a test of mathematical problem solving skills in the form of descriptions. Result: The analysis showed that there was a significant difference in mathematics problem solving ability between the group of students taught with PBI and the group taught with the Expository model. Specifically, the group using PBI showed a higher average problem solving ability than the Expository group. Novelty: This finding indicates that the Problem Based Instruction model is potentially more effective in developing mathematical problem solving skills.